Japanese Reanalysis for Three Quarters of a Century (JRA-3Q) Monthly Statistics ... - Japan Meteorological Agency, Japan (UCAR/NCAR - Research Data Archive, 2024)
JMA is currently conducting the Japanese Reanalysis for Three Quarters of a Century (JRA-3Q), which covers the period from September 1947 onward to extend the current period of data coverage and improve the quality of long-term reanalysis. The project involves a sophisticated data assimilation system (based on the operational set-up as of December 2018) incorporating development results from the operational NWP system and sea surface temperature analysis achieved since JRA-55 (based on the operational set-up as of December 2009). New datasets of past observations are also assimilated, including rescued historical observations and reprocessed satellite data supplied by meteorological and satellite centers worldwide. Many of the deficiencies of JRA-55 are alleviated in JRA-3Q, providing a high-quality homogeneous reanalysis dataset that covers the previous 75 years. ...